Transdermal delivery of combined hormonal contraception: a review of the current literature - Galzote RM; Rafie S; Teal R; Mody SK (Dove Medical Press, 2017)
Rosanna M Galzote,1 Sally Rafie,2 Rachel Teal,1 Sheila K Mody1 1Section of Family Planning, Department of Reproductive Medicine, University of California, San Diego, 2Department of Pharmacy, UC San Diego Health, San Diego, CA, USA Abstract: The transdermal patch provides an effective and convenient option for hormonal contraception. The patch currently on the US market contains 150 µg norelgestromin and 35 µg ethinylestradiol (EE). The 20 cm2 patch is applied once weekly for 3 weeks, followed by a patch-free week, for a 21–7 cycle. Typical failure rates are similar to that of combined oral contraceptives (COCs). Transdermal delivery results in less peaks and troughs of estrogen, but a higher total estrogen exposure compared with COCs. Though studies show mixed results, the risk of developing venous thromboembolism (VTE) is about twice as high with the patch as with COCs; however, the absolute risk of VTE remains low. The side effect profile is similar to that of COCs, with slightly higher rates of breast tenderness plus a unique adverse effect of application site reactions. Two new patches have been developed, one containing gestodene and EE in Europe and another containing levonorgestrel and EE. Overall, the patch provides an alternative to COCs for women who want autonomy and the benefit of not needing to take a pill daily, with similar efficacy and tolerability. Keywords: contraceptive patch, Ortho-Evra, transdermal, levonorgestrel patch, gestodene patch, hormonal patch